Structural complexity of hexagonal prismatic crystal specimens of fluorapatite‐gelatine nanocomposites: A case study in biomimetic crystal research. Issue 1 (19th November 2013) - Kniep, Rüdiger; Simon, Paul; Rosseeva, Elena
<x xml:space="preserve">Abstract</x> Hexagonal prismatic crystal‐like entities of fluorapatite‐gelatine nanocomposites were grown by double‐diffusion in gelatine gels. TEM images together with atomistic computer simulations reveal the material to be best described as a mosaic‐dominated nanocomposite superstructure. Intrinsic electric dipole fields, generated by the composite during its morphogenesis, cause the integration of a meso/macroscopic of gelatine microfibrils into the superstructure matrix. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>